2008
DOI: 10.1111/j.1742-4658.2008.06322.x
|View full text |Cite
|
Sign up to set email alerts
|

Hexadecylphosphocholine interferes with the intracellular transport of cholesterol in HepG2 cells

Abstract: We have shown, in a previous publication, that nontoxic concentrations of hexadecylphosphocholine exert an antiproliferative effect on HepG2 cells. Hexadecylphosphocholine also interferes with the biosynthesis of cholesterol and phosphatidylcholine. We have now extended our studies to try to establish the molecular mechanism by which hexadecylphosphocholine disrupts cholesterol homeostasis. Using radiolabelled substrates we determined the effect of hexadecylphosphocholine on cholesterol synthesis, the destiny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
(72 reference statements)
2
14
0
1
Order By: Relevance
“…Furthermore, the steady-state protein levels and mRNA expression of HMGCR and LDLR increased after incubation with the APC. HMGCR activity was not, however, directly modulated by miltefosine as assayed in vitro both in HepG2 cell lysates and rat-liver microsomes, and exposure of cells to miltefosine did not significantly affect the decay rate of the reductase [58]. On the other hand, incubation with miltefosine did not significantly change the expression of ACAT.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the steady-state protein levels and mRNA expression of HMGCR and LDLR increased after incubation with the APC. HMGCR activity was not, however, directly modulated by miltefosine as assayed in vitro both in HepG2 cell lysates and rat-liver microsomes, and exposure of cells to miltefosine did not significantly affect the decay rate of the reductase [58]. On the other hand, incubation with miltefosine did not significantly change the expression of ACAT.…”
Section: Reviewmentioning
confidence: 99%
“…However, cholesterol esterification from several radioactive exogenous fatty acids was markedly reduced after treatment with miltefosine, even in the presence of the cholesterol analog 25-hydroxycholesterol added to the culture medium; in addition, the reesterification rate of cholesterol from LDL decreased after treatment with the APC [35,58]. This inhibition of intracellular CE synthesis was observable after only one hour of exposure to miltefosine [39].…”
Section: Reviewmentioning
confidence: 99%
“…In leukemic cells treatment with alkylphospholipids induces the formation of membrane raft aggregates containing Fas/CD95 death receptor and the adaptor molecule Fas-associated death domain-containing protein (FADD), which are critical in the triggering of apoptosis (Gajate et al, 2009). Miltefosine and other alkylphospholipids also alter intracellular cholesterol traffic and metabolism leading to an increased uptake, synthesis and accumulation of cholesterol in the cell (Carrasco et al, 2008;Jimenez-Lopez et al, 2006;Marco et al, 2009). As cholesterol and sphingomyelin content are critical for the integrity and functionality of membrane lipid rafts, the disturbance of the cholesterol/sphingomyelin ratio could alter signaling pathways associated with these membrane domains.…”
Section: Uptake and Absorption Of Alkylphospholipidsmentioning
confidence: 99%
“…An important characteristic of APLs is their amphiphilic properties, enabling them to interact with cell membranes and affect cell metabolism at different levels (reviewed by . Within this context, studies carried out in our laboratory have demonstrated that, after long-term treatment, the APL hexadecyl 2-(trimethylazaniumyl)ethyl phosphate (hexadecylphosphocholine; HePC), also known as miltefosine, alters phosphatidylcholine metabolism (Jimé-nez-López et al, 2004) and intracellular cholesterol trafficking and metabolism, all of which lead to an increased uptake, synthesis, and accumulation of cholesterol in the cell (Jimé-nez-López et al, 2006;Carrasco et al, 2008;Marco et al, 2009). Thus, we extended our studies to analyze the effects of a variety of APLs, such as [1-O-octadecyl-2-O-methyl-racglycero-3-phosphocholine] (edelfosine), [(Z)-docos-13-enyl] 2-(trimethylazaniumyl)ethyl phosphate (erucylphosphocholine; ErPC), and 1,1-dimethylpiperidin-1-ium-4-yl) octadecyl phosphate (perifosine) upon intracellular cholesterol homeostasis and found that all of them impede the esterification of plasma-membrane cholesterol via acyl-CoA/cholesterol acyltransferase activity .…”
Section: Introductionmentioning
confidence: 99%